Fikih Organisasi (Reaktualisasi Sejarah Nahdlatul Ulama (NU) di Indonesia) - Ulum , Miftahul; Wahid , Abd (LPPPM STAI Darul Hikmah Bangkalan, 2019)
Historical facts state that NU was an organization that was originally founded by religious scholars of pesantren, before the birth of NU in Surabaya in 1926. In 1961 as the golden age of the beginning of the nation's awakening (Nahdlatul Wathon) because at that time Indonesia was under colonialist rule, the pesantren religious scholars as the central figure in the struggle for independence of the Unitary Republic of Indonesia no longer prioritized the Islamic group which was limited, but rather a universal policy for the rise of the nation and in the context of the struggle to drive out colonialism. In its historical roots, as a center of freedom movement fighters, Nahdlatul Wathon was then followed by the establishment of Nahdlatut Tujjar (Resurrection of Traders) which was an attempt by the religious scholars to build and develop the economic independence of the community, rival and drive out the economic development of the colonizers. Nahdlatut Tujjar's struggle which later became a practical warrior in the economic sector, in addition to his struggle in the national sector through Nahdlatul Wathon. The NU Autonomous Agency is an NU Organizational Tool that functions to help implement NU policies, especially those relating to disadvantaged communities. The autonomous bodies referred to include: Fatayat NU, Muslimat NU, GP Ansor, IPNU, IPPNU, Jam'iyan Expert Thariqah al Mu'tabaroh an Nahdliyah, JQH (Jamiyatul Quro 'wal Hufadz), Pergunu (Nahdlatul Ulama Teachers' Association) , and ISNU (Nahdlatul Ulama Bachelor Association).